Kerjasama Tim Terhadap Cidera Olahraga Bolabasket - Gigih Siantoro, (Kepelatihan Olahraga, 2010)
Basketball players is a team player or team, it would require good cooperation from the players, to establish good cooperation, each player is expected to have basic technical skills of basketball game that consists of: throwing and catching techniques, dribbling the ball, shooting techniques, pivot and foot work. Cooperation is the willingness to cooperate with others in a cooperative and become part of the basketball team. Not working in isolation or competing. Competence partnership emphasizes the role as a member of the team, not as a leader. Prevention of sports in general requires the development of concepts related to activities in an integrated program. Athletes and coaches should always take into consideration the physical and mental changes that occur in the body of an athlete nor a place of good cooperation exercise a basketball team from the manager, coach, Sports medicel, and Doctor. Basketball coaches need to know the causes of injury and understand how and why there was a specific injury and how to prevent it.